Effectiveness of a pain science education programme in middle school students: a randomised controlled trial - Menés Fernández, Laura; Salvat, Isabel; Adillón, Cristina (Frontiers in Public Health, 2025)
IntroductionChronic pain in childhood is a prevalent issue affecting approximately 20% of young people aged 8–16 years. This condition negatively impacts their quality of life, as well as their physical, psychological, and social functioning. In recent years, Pain Science Education has emerged as a promising strategy to enhance the conceptualization of pain and mitigate maladaptive pain-related behaviours in children and teenagers. The primary aim of this study is to assess the effectiveness of the Pain Science Education programme called “Learning Pain” in improving the conceptualization of pain amongst 11–13-year-old children enrolled in their first year of middle school.Materials and methodsA randomised controlled trial with single-blind parallel groups was conducted. Five participating institutes were randomly assigned to either the experimental group, which received the Pain Science Education intervention through the “Learning Pain” programme consisting of two sessions spaced 1 month apart, or the control group, which underwent only study assessments. Both groups underwent initial assessment and follow-up evaluations at 1 month (short term), 7 months (medium-term), and 13 months (long-term). The main outcome measure was the conceptualization of pain, assessed using the Conceptualization of Pain Questionnaire (COPAQ).ResultsThe “Learning Pain” programme, a specific Pain Science Education intervention, demonstrated effectiveness in improving the conceptualization of pain at 1, 7, and 13 months follow-up assessments.DiscussionThe “Learning Pain” programme, a specific Pain Science Education intervention, enhances the conceptualization of pain in adolescents aged 11–13 years over short, medium, and long-term periods.